Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/1403494815569867
|View full text |Cite
|
Sign up to set email alerts
|

Vigorous physical activity rather than sedentary behaviour predicts overweight and obesity in pubertal boys: A 2-year follow-up study

Abstract: The results indicate that vigorous PA in particular predicts overweight and obesity in boys. They should aim to do at least 60 minutes per day of MVPA. These results contribute to the recommendations suggesting that a minimum of 15 minutes per day of vigorous PA is desired to reduce the risk of developing overweight/obesity in later puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 28 publications
3
69
0
Order By: Relevance
“…The project invitation was then given to each boy of particular classes in those schools who agreed to participate and approximately 84% of them agreed to take part. Initial exclusion criteria were different health problems that did not allow the potential subjects to participate in physical education classes [15,25]. All participants were thoroughly informed of the purposes and contents of the project and a written informed consent was obtained from the parents before participation in the project.…”
Section: Methodsmentioning
confidence: 99%
“…The project invitation was then given to each boy of particular classes in those schools who agreed to participate and approximately 84% of them agreed to take part. Initial exclusion criteria were different health problems that did not allow the potential subjects to participate in physical education classes [15,25]. All participants were thoroughly informed of the purposes and contents of the project and a written informed consent was obtained from the parents before participation in the project.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies found that sedentary time predicted lower BMI (17) and WC (39), even after adjustment of MVPA. In general, studies examining the prospective associations between sedentary time and adiposity reported no evidence for any association (16,27,28,(33)(34)(35)(36)(37)(38). Activity of at least moderate intensity was inversely associated with BMI (36,38,40,41) and WC (18,39).…”
Section: Adipositymentioning
confidence: 97%
“…However, differences between boys and girls were present, as an inverse association was evident between vigorous PA and WC in boys only (18). Moreover, boys not meeting the threshold of 20 min of vigorous PA at baseline had an increased risk for overweight 2 years later (OR = 4.14) (37). However, half of the studies found no prospective associations between MVPA at baseline and BMI (42,43) or WC (16,27,28,33,40,42) in models that were ultimately adjusted.…”
Section: Adipositymentioning
confidence: 98%
“…Surprisingly, little is known about the sRPE responses in adolescents and more research is needed to better understand the perceptual responses and the optimal rating scale to use in this age group. This is significant given that adolescence is usually a time when a child's level of physical activity begins to decline [32]. Knowledge of a perception of exercise and the physiological factors mediating perceived exertion in this age group and how it might change with further maturation may be important in optimising training loads, promoting healthy physical activity and exercise recommendations and to prevent child from dropping out of sport.…”
Section: Training Load Measurement In the Prevention Of Injuriesmentioning
confidence: 99%
“…One possible reason for this discrepancy might be the experience of the athlete [12] as correlations have been shown to increase when athlete matures. However, ITL might be affected, at least in adolescents, by factors outside from planned workout such as habitual physical activity or the involvement in other sport trainings [12], which might result in more than 5-time difference in moderate-tovigorous physical activity between subjects [32]. Furthermore, accumulation of fatigue and sleep loss or deprivation can have significant effects on performance, motivation, perception of effort and cognition [27].…”
Section: Monitoring Training Load -Difference Between Athlete and Coachmentioning
confidence: 99%